Development of Physical Education Learning Outcomes Assessment Instruments for Volleyball Materials Based on Game Performance Assessment Instrument - Dewanti, Galih; Nompembri, Soni; Widiyanto; Hartanto, Amri; Arianto, Afeb Chesa (Physical Education Theory and Methodology, 2023)
Study purpose. The basic assumption of this development is that there is no Game Performance Assessment Instrument (GPAI) based on physical education (PE) learning outcome assessment, so researchers are trying to develop the instrument. The teacher has not used the GPAI instrument in assessing the PE learning outcomes for volleyball material. The purpose of the study was to develop a valid and reliable assessment of PE learning outcomes for volleyball based on GPAI. Materials and methods. This type of research is research and development. The subjects used were PE learning expert lecturers and volleyball expert lecturers with a minimum qualification of 5 Doctoral degrees. The field test was conducted on 18 junior high school students. The instrument uses a questionnaire with a score of 1-4 with the terms “Very Appropriate (score 4)”, “Agreed (score 3)”, “Not Appropriate (score 2)”, and “Very Not Appropriate (score 1)”. The validity data analysis technique uses Aiken validity, and reliability tests are carried out using Intraclass Correlation Coefficients. Results. Based on the results of the research and the results of the data analysis that has been carried out, it is concluded that the instrument for assessing the learning outcomes of PE on volleyball material in Junior High School based on GPAI that was developed is valid and reliable, with V Aiken ≥ 0.87. Furthermore, the reliability of the PE learning outcomes assessment instrument for volleyball material in GPAI-based junior high schools was 0.797 in the "High" category. Conclusions. The researcher hopes that the resulting product in the form of an assessment of PE learning outcomes for volleyball material in junior high schools based on the GPAI can be a guide or reference for evaluating students on volleyball material.